An Overview Of The Reproductive Health Of Teenage Girl In The Bereng Bengkel Village - Munanadia, Munanadia (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Adolescence is a period of change or transition from childhood to adulthood. WHO defines adolescents as individuals who experience a transitional period gradually reaching sexual maturity. BPS 2022 data estimates that youth in Indonesia is equivalent to 24% of the total population. Healthy adolescents are an investment for the nation's future to meet the demographic bonus in 2030. Young women must be introduced to reproductive health so that adolescents know what is happening to themselves, especially those related to the reproductive organs which are used as determinants of size. a measure of health parameters and used as an indicator of the success or failure of programs to reduce stunting and reduce maternal and infant mortality. This study aims to determine the description of the health of Teenage Girl in the Bereng Bengkel Village. This type of research is descriptive with a quantitative approach. A total of 61 teenage girl aged 10-20 years as a population and the sampling technique was "Accidental sampling" and found 37 teenager. Data analysis using SPSS, obtained the results of Teenage Girl behavior (consumption of FE tablets 64,9%), information on reproductive health (reproductive organs 67,6%, characteristics of puberty 86,5%, pregnancy 48,7%, impact of free sex 62,1%, STI 64,9%, HIV 51,3% , and Personal Hygiene 75,7%). Regarding menstruation (menarche at the age of 11-16 years 73%, regular menstrual cycles 86,5%, no dysmenorrhea 81,1%, and no reproductive health problems such as vaginal discharge, etc. 73%). Furthermore, Teenage Girl plan to marry at the age of 20-35 years (73%), and participate in PKPR activities (81,1%). Reproductive health for teenage girl in the Bereng Bengkel Village is a responsibility and needs an important role from the family, school, government, to related stakeholders.